PENGEMBANGAN MODEL MANAJEMEN PELATIHAN GURU MATA PELAJARAN BAHASA DI SMP UNTUK MENINGKATKAN KINERJA GURU: ANALISIS NEED ASSESSEMENT, KINERJA, DAN RANCANGAN MODEL - Padlurrahman, Padlurrahman (Universitas Hamzanwadi, 2009)
This reserach aimed at designing a model of in service-trainning management for the Indonesian Language Teachers at junior hig School in East Lombok. It was developed through paradigm of a system approach-based total quality management. The total pupolation are 178 teachers at 52 State Junior High School (SJHS) in East Lombok. This reserach used qualitative approach. The primary data were collected by using questionnaire and the secondary data were collected by using interview and observation. The data were anlayzed based on the Nasution’s model analysis, such data reduction, data display, and conclusion or verification for all types of the data. The research results proved that (1) the profile needs of in service-language teacher trainning at SMP in East Lobok regency is in the form of a systemic components which can give a positive contribution on the planning of its program; (2) most of the teachers have positive attitudes on their professions as teachers, while the percentage of their knowledge and skill aspects is average although the mean is more than 50%; and (3) a model of in service-language teacher trainning at SMP in East Lombok regency produced a quality mannual, procedure manual, and instructions of in service trainning. All of the steps need a measurable quality documents through an audite of quality assurance on each component of their system. Some advantages of this design are (1) the provider of in service-language teacher trainning may play an important role as a quality assurance institution; (2) mastery on each quality assurance aspect can be done; and (3) the measurement of the service effect can be held although it has finished. Keywords: Training Management, Teachers’ Performance.